Experience of endovideosurgical method in treatment of patients with inguinal hernias - V. V. Strizheletskiy; S. A. Makarov; A. B. Lomiya (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. This article analyzed the results of surgical treatment of patients who underwent laparoscopic hernioplasty. MATERIAL AND METHODS. The results of surgery of 1303 patients with inguinal hernia were assessed. All the patients were operated on in City Centre of Innovative Medical Technologies at the period from March 2013 to December 2016. Laparoscopic prosthetic hernioplasty using mesh prosthesis was carried out on 1199 patients. Traditional Liechtenstein hernia repair had 104 patients. RESULTS. The research showed that laparoscopic hernia repair had greater clinical efficacy as compared with traditional hernia repair. It appeared to be preferable choice of surgical treatment of inguinal hernias of any complexity.